Arbitrary Suspect Designation In Corruption Cases The Legal And Human Rights Implications - Nugraha, Roby Satya; Iskandar, Eka Ardianto; Siswajanthy, Farahdinny; Darmawan, Iwan; Suhermanto, Suhermanto; Wuisang, Ari (UNIVERSITAS PAKUAN, 2025)
ABSTRACTThe determination of a suspect constitutes a legal act by investigators that alters a person’s status from not being linked to a criminal offense into someone who is reasonably alleged to have committed one. This study arises from the Attorney General’s Office’s decision to designate Thomas Trikasih Lembong as a suspect, which was not in accordance with the provisions of the Indonesian Criminal Procedure Code (KUHAP). The research adopts a normative legal method complemented by empirical analysis, relying on secondary sources (literature) and interviews with relevant parties. The theoretical framework employed is based on the Theory of Legal Protection and Progressive Law Theory, which underpin the analytical approach in achieving the research objectives. The findings reveal that the suspect designation against Thomas Trikasih Lembong lacked sufficient preliminary evidence, as the prosecutors failed to prove any actual state financial loss attributable to him. Moreover, the legal provision invoked by the Attorney General’s Office did not meet the required elements of a corruption offense. The study concludes that law enforcement authorities must exercise their powers in compliance with existing legal rules to guarantee both legal certainty and a fair sense of justice for all individuals. Keywords: Corruption, Suspect Designation, Attorney General’s Office, Legal Certainty, Pretrial.